FAST MIGRATION/INVERSION WITH MULTIVALUED RAYFIELDS: PART 1 - METHOD, VALIDATION TEST, AND APPLICATION IN 2D TO MARMOUSI - Xu S.; Lambaré G. (My University, 2004)
We address the problem of building an efficient algorithm for ray-based migration/inversion in complex media characterized by multivalued traveltime. Since the multivalued ray maps can be computed by wavefront construction, the key point lies in the interpolation of these multivalued coarse maps. For this goal we propose two new strategies. The first one is based on an interpo-lation of the rayfield after identifying the ray branches on the elementary cells of the coarse grid; the second is based on an extrapolation of the arrivals from the coarse grid points. Both strategies are evaluated in two dimensions with the Marmousi data set, demonstrating the CPU efficiency and accuracy of both approaches. Since they both consider multiarrivals locally, the associated overhead cost with respect to a single-arrival implementation is quite low (twice the computing time of the Marmousi test case). The application also reveals that the new interpolation strategy is more efficient in terms of CPU time compared to the extrapolation strategy but at the expense of a more complex numerical implementation and less accurate results.